Pengaruh Struktur Modal, Perencanaan Pajak, Firm Growth, dan Investment Opportunity Set terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Sub Sektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia Periode 2020 – 2024) - Ningrum, Masayu Purbo; Puspita Rani (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This research examines the impact of capital structure, tax planning, firm growth, and investment opportunity set on firm value in food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. A quantitative approach was employed using secondary data derived from annual financial reports. The sample was selected through purposive sampling, resulting in 33 firms. The data were analyzed using multiple linear regression techniques. The findings indicate that capital structure, firm growth, and investment opportunity set positively and significantly influence firm value. In contrast, tax planning, measured by the effective tax rate, shows a negative and significant effect on firm value. These results suggest that financing policy, growth performance, and investment prospects are key drivers of firm value, while more aggressive tax planning strategies tend to be viewed less favorably by the market.